Diurnal evolution of solar radiation at the surface in the city of São Paulo: Seasonal variation and modeling - Oliveira, A. P. de; Machado, A. J.; Escobedo, João Francisco [UNESP]; Soares, J. (Springer Nature, 2002)
Seasonal variations in the diurnal evolution of the global, diffuse and direct solar radiation at the surface, the clearness index, diffuse fraction and direct fraction are described in detail for the City of Sao Paulo, Brazil. The description is based on measurements of global and diffuse solar radiation carried out over 5.25 years. The diffuse component was measured with a shadow-band device. The annual evolution of the amplitude of the diurnal cycle of all radiometric parameters indicates a seasonal pattern with two distinct periods: autumn-winter and spring-summer. About 10% of the observed period was characterized by clear sky days. This seasonal variation is determined by a larger incidence of clear sky days in the autumn-winter period. Reductions of up to 10% in hourly and daily values of global radiation were observed in conjunction with an increase in particulate matter concentration on clear sky days. The pollution effect may be responsible for the discrepancy, of 16%, found between local and more regional estimates of global solar radiation in Sao Paulo. The diurnal evolution of hourly values of monthly-averaged global and diffuse solar radiation were successfully estimated by the empirical expressions derived here. Daily values of monthly-averaged global solar radiation were satisfactorily estimated using the Angstrom expression.
Keywords: diurnal variation; modeling; seasonal variation; solar radiation; urban area; Brazil